The Formation of the Individual Performance Style of a Future Master of Musical Arts While Preparing for Concert Performance: an Interpretive Aspect - Malakhova, Marharyta (Educological discourse, 2024)
The article highlights the problem of how a master of musical arts develops their performance style while preparing for concert performances in terms of the interpretive aspect of musical-creative activity. The topicality of the research is determined by the dynamics of performing arts development and, as a result, the ongoing interest of scientists, music educators, and practicing teachers in enhancing musicians’ performance skills in general and performance style in particular. The purpose of this research is to examine the phenomenon of style in the performing arts, to emphasize the ways in which a master of musical arts develops their performance style in the lead-up to a concert, and to support the impact of the performer’s interpretative activity on the process of preparation. The research methodology is based on the complex application of methods of analysis of scientific resources, generalization of theoretical provisions, synthesis and systematization of received information; using scientific approaches: competence-based, person-oriented, practice-oriented, hermeneutic, and consolidation approaches. During the study, the definition of "performance style" has been examined, and its characteristics have been described in the context of the educational process of instrumental and performance training for a master of musical arts. The syllabus of the discipline "Special Instrument" has been discovered to cover three modules, the content of which is developed under the logic of preparing a musician-performer for a concert performance and achieving a long-term result in the formation of the performance style of a master of musical arts. The content of the first module focuses on issues pertaining to repertoire selection and technical problem-solving when studying the program’s musical pieces. The content of the second module reveals the phenomenon of self-regulation in the process of musical performance and the interpretative activity of the performer. It also defines terms such as musical performance thinking, the artist’s empathic-sensual sphere, creative intuition, and artistry. The third module covers the pre-concert phase of a musician’s stage performance. According to the conclusion, the process of preparing a master of musical arts for concert performance creates optimal conditions for the development of an artist’s personality, serves as a creative field for testing various variants of performing concepts, gaining stage experience, and, ultimately, plays a significant role in the formation of the performing style.